U.B.S.P. programme in Vizianagaram town - an appraisal - Rao, P. Subba (2000)
The phenomenal growth of population in the million plus cities and urban agglomeration cause heavy pressure on the social, economic and environmental infrastructures. This results in the emergence of slums and scatter settlements. The population of Vizianagaram town has increased from 14m806 in 1981 to 1,60,359 in 1991 with the increase of 39.7 per cent. According to the socio-economic survey conducted by the Government of Andhra Pradesh in 1994, 65 slums are identified covering a total population of 66,806. The Government of Andhra Pradesh has selected Vizianagaram town for the implementation of Urban Basic Services for Poor (UBSP) programme to improve the qualaity of life of slum dwellers from May 1991. The programmes implemented by the UBSP are classified into 4 sections: 1. Physical Infrastructure, 2. Social Development, 3. Income Generating Activities and 4. Health Input. Under Physical infrastructure, community halls were constructed for each slum, provided colour television sets; provided drinking water and also constructed roads drains, street lighting, etc. Under social development programmes, UBSP provided pre-primary education, non-formal education and vocational training. Under income generating activities, UBSP provided several training programmes to the slum dwellers (especially for the women) in the trades like cane furniture making, banjara needle craft, mesta handicrafts, agarbatti making, book binding, bakery products, computer training etc., Under health input, UBSP provided awareness on several community development programmes like immunisation, health and hygiene, sanitation, literacy etc. - Reproduced
Keywords: Slums - India - Andhra Pradesh; Urban development - India - Andhra Pradesh; Urban development